Carboxyhemoglobin (CO-Hb) correlates with hemolysis and hospital mortality in extracorporeal membrane oxygenation: a retrospective registry - Bemtgen, Xavier; Rilinger, Jonathan; Holst, Manuel; Rottmann, Felix; Lang, Corinna N.; Jäckel, Markus; Zotzmann, Viviane; Benk, Christoph; Wengenmayer, Tobias; Supady, Alexander; Staudacher, Dawid (Diagnostics, 2022)
Background: Patients supported with extracorporeal membrane oxygenation (ECMO) may develop elevated carboxyhemoglobin (CO-Hb), a finding described in the context of hemolysis. Clinical relevance of elevated CO-Hb in ECMO is unclear. We therefore investigated the prognostic relevance of CO-Hb during ECMO support. Methods: Data derives from a retrospective single-center registry study. All ECMO patients in a medical ICU from October 2010 through December 2019 were considered. Peak arterial CO-Hb value during ECMO support and median CO-Hb values determined by point-of-care testing for distinct time intervals were determined. Groups were divided by CO-Hb (<2% or ≥2%). The primary endpoint was hospital survival. Results: A total of 729 patients with 59,694 CO-Hb values met the inclusion criteria. Median age (IQR) was 59 (48-68) years, 221/729 (30.3%) were female, and 278/729 (38.1%) survived until hospital discharge. Initial ECMO configuration was veno-arterial in 431/729 (59.1%) patients and veno-venous in 298/729 (40.9%) patients. Markers for hemolysis (lactate dehydrogenase, bilirubin, hemolysis index, and haptoglobin) all correlated significantly with higher CO-Hb (p < 0.001, respectively). Hospital survival was significantly higher in patients with CO-Hb < 2% compared to CO-Hb ≥ 2%, evaluating time periods 24-48 h (48.6% vs. 35.2%, p = 0.003), 48-72 h (51.5% vs. 36.8%, p = 0.003), or >72 h (56.9% vs. 31.1%, p < 0.001) after ECMO cannulation. Peak CO-Hb was independently associated with lower hospital survival after adjustment for confounders. Conclusions: In ECMO, CO-Hb correlates with hemolysis and hospital survival. If high CO-Hb measured should trigger a therapeutic intervention in order to reduce hemolysis has to be investigated in prospective trials.
Gesehen am 19.08.2022